Methods of teaching foreign languages in the educational process - et. al., Qulaxmedova Gulnora Abduraximovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Educating the younger generation physically healthy, intellectually developed, independent-minded, strong-willed, loyal to the Fatherland, deepening democratic reforms and increasing their social activity in the development of civil society are identified as important tasks in the Action Strategy for 2017-2021.